Pelatihan sepak bola yang inovatif: Model turnamen permainan tim berbasis Android - Mulawarman, Andi; Ihsan, Andi; Mustafa, Mustafa; Mappaompo , M. Adam; Aprilo, Ians (Universitas Nusantara PGRI Kediri, 2024)
In the digital era, traditional soccer training often fails to engage tech-savvy students, requiring innovative approaches like Android-based tournament models. By integrating technology with cooperative learning, these models enhance students' soccer skills, strategic understanding, and motivation. This study aims to see the effect of developing the Team Games Tournament (TGT) method with Android-based online games in improving students' understanding of playing soccer. This research method uses the ADDIE model as a framework for making products, with a quantitative approach used to process data obtained through questionnaires in the form of descriptive percentages. The sample involved in this study were 32 students, the sampling technique used was purposive sampling. The results of this study indicate that there is an effect of the pakgolo learning model in improving students' understanding of playing soccer, this is reinforced by the results of the sigs (2-tailed) analysis with a sig (2-tailed) value of 0.000 which means that the sig (2-tailed) value <0.05. With the value of tcount = -19.402 with df = 126 so that the ttable = -28.503 is obtained. The conclusion of this study provides a unique method with a combination of technology and cooperative learning, which is rarely widely applied, especially in soccer learning. The contribution of this study adds a new method that can improve skills with a very fun method so that students easily understand the learning material.